PEMBENTUKAN DAN PELATIHAN KANJI (KADER KESEHATAN JIWA) UNTUK MEWUJUDKAN DESA SIAGA SEHAT JIWA BERBASIS KOMUNITAS - Indri Yati; Herawati, Vitri Dyah; Putri, Dhian Riskiana (P3M Universitas Aisyiyah Surakarta, 2024)
Handling people with mental disorders (ODGJ) is a problem that spreads in all regions because 1 in 10 people with ODGJ live around us. Based on the Law of the Republic of Indonesia No. 18 of 2014 concerning Mental Health in which every activity realizes optimal mental health degrees for individuals, families, and communities with promotive, preventive, curative, and rehabilitative approaches which are carried out comprehensively and sustainably by the Government, Regional Governments and the community. This activity aims to improve the health status of ODGJ and provide health services for ODGJ. Referring to the achievement targets above, the approach method used in this PKMS activity is to hold the selection of mental health cadres (KANJI) and conduct trainings for mental health cadres such as how to detect family mental health status, mental health programs, determine mental health interventions in the community. community, how to handle violent behavior in the community, mobilizing cadres to make home visits as well as recording and reporting the results of detection of mental health status in the community. This activity was then continued by providing assistance to the participants so that this activity could continue and form a mental health studio as a forum for ODGJ to carry out activities to provide non-pharmacological therapy or without drugs and establish collaboration with the puskesmas and local village stakeholders.